2011
DOI: 10.2214/ajr.10.5390
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Hypointense Hepatocellular Nodules Observed Only in the Hepatobiliary Phase of Gadoxetate Disodium–Enhanced MRI

Abstract: Hypointense nodules with a maximum diameter of at least 15 mm often become hypervascular. Therefore, patients with hypointense nodules characterized by a maximum diameter of 15 mm or greater should be observed carefully because of the high incidence of vascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
138
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(157 citation statements)
references
References 24 publications
11
138
6
Order By: Relevance
“…This comparative study confirmed the dedifferentiation of HCC with tumor growth (10). Concerning the progression, Kumada et al (11) demonstrated recently that hypointense hepatocellular nodules with maximum diameters ! 15 mm in the hepatobiliary phase of gadolinium-ethoxybenzyl-diethylenetriamine pentaacetic acid enhanced magnetic resonance imaging (Gr-EOB-MRI) become hypervascular (vascularized nodules) at rates of 43.3% and 77.3% during 6 months and 12 months, respectively.…”
Section: Statistical Analysessupporting
confidence: 78%
“…This comparative study confirmed the dedifferentiation of HCC with tumor growth (10). Concerning the progression, Kumada et al (11) demonstrated recently that hypointense hepatocellular nodules with maximum diameters ! 15 mm in the hepatobiliary phase of gadolinium-ethoxybenzyl-diethylenetriamine pentaacetic acid enhanced magnetic resonance imaging (Gr-EOB-MRI) become hypervascular (vascularized nodules) at rates of 43.3% and 77.3% during 6 months and 12 months, respectively.…”
Section: Statistical Analysessupporting
confidence: 78%
“…In a radio-pathologic correlation study including 111 indeterminate hepatocellular nodules on Gd-EOB-DTPA MRI, Golfieri et al have found 60 benign lesions, 41 premalignant lesions (high-grade dysplastic nodules/early HCC), and 10 HCCs, and concluded that hepatobiliary phase hypointensity is the stronger marker of malignancy [9]. The latter observation is in accordance with a paper by Kumada et al, which have reported that approximately one quarter of Gd-EOB-DTPA hepatobiliary phase hypointense hepatocellular nodules became hypervascular HCCs at follow-up [10]. Moreover, Kim et al have found that hyperintensity on diffusion-weighted (DW) images in hypovascular hepatobiliary phase hypointense nodules increased the risk of progression to hypervascular HCCs [11].…”
Section: Introductionsupporting
confidence: 68%
“…80,81 If left untreated, more than 10z of these lesions will become hypervascular or conventional HCCs within a year. Among early HCCs identiˆed by gadoxetic acid-enhanced MR imaging, an especially important risk factor for hypervascularization is size exceeding 10 mm 87,88 (Fig. 9a-d).…”
Section: Room For Discussionmentioning
confidence: 99%